Novel Peptide-Based PD1 Immunomodulators Demonstrate Efficacy in Infectious Disease Vaccines and Therapeutics - Kotraiah, Vinayaka; Phares, Timothy W.; Browne, Cecille D.; Pannucci, James; Mansour, Marc; Noe, Amy R.; Tucker, Kenneth D.; Christen, Jayne M.; Reed, Charles; MacKay, Alecia; Weir, Genevieve M.; Rajagopalan, Rajkannan; et al. (Frontiers in Immunology, 2020)
Many pathogens use the same immune evasion mechanisms as cancer cells. Patients with chronic infections have elevated levels of checkpoint receptors (e.g., programed cell death 1, PD1) on T cells. Monoclonal antibody (mAb)-based inhibitors to checkpoint receptors have also been shown to enhance T-cell responses in models of chronic infection. Therefore, inhibitors have the potential to act as a vaccine “adjuvant” by facilitating the expansion of vaccine antigen-specific T-cell repertoires. Here, we report the discovery and characterization of a peptide-based class of PD1 checkpoint inhibitors, which have a potent adaptive immunity adjuvant capability for vaccines against infectious diseases. Briefly, after identifying peptides that bind to the recombinant human PD1, we screened for in vitro efficacy in reporter assays and human peripheral blood mononuclear cells (PBMC) readouts. We first found the baseline in vivo performance of the peptides in a standard mouse oncology model that demonstrated equivalent efficacy compared to mAbs against the PD1 checkpoint. Subsequently, two strategies were used to demonstrate the utility of our peptides in infectious disease indications: (1) as a therapeutic in a bacteria-induced lethal sepsis model in which our peptides were found to increase survival with enhanced bacterial clearance and increased macrophage function; and (2) as an adjuvant in combination with a prophylactic malaria vaccine in which our peptides increased T-cell immunogenicity and the protective efficacy of the vaccine. Therefore, our peptides are promising as both a therapeutic agent and a vaccine adjuvant for infectious disease with a potentially safer and more cost-effective target product profile compared to mAbs. These findings are essential for deploying a new immunomodulatory regimen in infectious disease primary and clinical care settings.